Clinical evaluation of meibomian gland dysfunction in patients with keratoconus. Issue 3 (June 2022) - Martínez-Pérez, Laura; Viso, Eloy; Touriño, Rosario; Gude, Francisco; Rodríguez-Ares, María Teresa
Abstract: Purpose: To investigate the association of keratoconus (KC) with meibomian gland dysfunction (MGD) and to describe the epidemiological characteristics of MGD in this disease. Methods: In this observational study, 120 KC patients seen in the Department of Ophthalmology of the Complexo Hospitalario Universitario de Santiago de Compostela and 87 controls were analyzed. The Ocular surface disease index (OSDI) questionnaire was administered and several DED tests and an evaluation of the meibomian glands and lid margin were performed. MGD signs and DED tests were compared between the groups. Symptoms were further analyzed in patients and controls with and without MGD. Results: KC was significantly associated with MGD after adjusting for age and sex [adjusted odds ratio (ORa), 2.40]. The frequency of MGD in KC patients [59 (49.2%) KC patients and 25 (28.7%) controls had MGD] correlated with the severity of KC (r = 0.206) ( P  = 0.020). Mean OSDI score in KC patients with and without MGD was 31.1 ± 24.1 and 35.2 ± 26.0 ( P  = 0.326), and 17.2 ± 22.7 and 13.3 ± 14.1 in controls with and without it ( P  = 0.366). The most common MGD signs coincided in both groups. Staining with fluorescein ( P  = 0.000) and lissamine green ( P  = 0.019) was higher in KC patients, but no differences were detected with TBUT ( P  = 0.116) or the Schirmer test ( P  = 0.637). Hypersecretory MGD was the most prevalent variant in both groups. Conclusions: MGD and DED are common in KC patients. MGD correlates with the severity of KC and is indistinguishable from MGD in patients without KC. No association was found with symptoms. Patients with KC should be screened for MGD because of its possible clinical implications. Further research is needed to clarify the role of MGD in KC patients.